Facilitating the use of virtual worlds in schools - Iqbal, Ahmer (2012)
Virtual worlds have grown in popularity recently and thus have been able to gain attention of many researchers and educationists as well. Despite that many educationists believe that virtual worlds could be a beneficial educational technology, it has not been widely implemented in schools. This dissertation seeks to explore the issues related to facilitating the use of virtual worlds in schools. There are two main goals in this dissertation. First goal is to identify the participatory practices of the participants in virtual worlds which can be informed to the educationists so that they can use appropriate participatory practices according to their needs. Secondly, the issues that teachers and administrators need to consider in facilitating the use of virtual worlds in schools including the choice of different instructional delivery methods. The dissertation consists on an introduction or summary and a collection of six articles. First four articles help in identifying the participatory practices. Fourth article also contributes to the second goal as well as the fifth and sixth articles. Sixth article compares different instructional delivery methods. During this research, participants from five Finnish and a Pakistani school participated during different phases. In this research mostly mixed-methods were used. The dissertation builds upon a thorough literature review and results obtained from the research to identify the participatory practices and generate recommendations that educationists need to consider in facilitating the use of virtual worlds in schools. A framework of educational facilitation in virtual worlds is suggested. The dissertation also includes a discussion on the process of facilitation of virtual worlds in schools. Finally, this dissertation recommends some future research areas and directions to further the cause of facilitating the use of virtual worlds in schools.